Gambaran dislipidemia pada pasien stroke akut di RSUD Arifin Achmad Provinsi Riau Periode Januari-Desember 2019 - Dimas Pramita Nugraha; Eka Bebasari; Sahwal Sahputra (Jurnal Kedokteran Syiah Kuala, 2021)
Stroke is a disease of the brain functional disorders that arises suddenly and lasts more than 24 hours or ends in death situation without a known cause other than vascular disorders. Strokes are generally classified into ischemic stroke (non-hemorrhagic) and hemorrhagic stroke, One of the risk factors of stroke is dyslipidemia. The aim of this study was to describe dyslipidemia in acute stroke patients at Arifin Achmad Regioal General Hospital of Riau Province in January to December 2019. This was a descriptive study design with cross sectional study method by using secondary data of the acute stroke patient's medical record at Arifin Achmad Regional General Hospital of Riau Province in January to December 2019 with a total sample of 103 cases. The results show that stroke is more common in male that is 63 (61.2%) cases, and the majority happened within the 51-65 years age groups with 54 (52.4%) cases. Most of the stroke’s type in patients were hemorrhagic stroke in 59 (57.3%) cases. Highest total of cholesterol level remains normal in 46 (44.7%) cases. The majority of patients still presented with normal level of High Density Lipoprotein (HDL) in 49 (47.6%) cases. In contrary, most patients presented with high level of Low Density Lipoprotein (LDL) in 26 (25.2%) cases and also with normal level but considered as high-risk group in  26 (25.2%) cases. Most patients still presented with normal level of triglyceride in 65 (63.1%) cases. There were 17 (16.5%) cases of patient with dyslipidemia, 9 of them were considered as ischemic stroke (52.9%). The conclusion of this study is that dyslipidemia commonly occurs in ischemic stroke types compared to a hemorrhagic stroke. Keywords: dyslipidemia, stroke, non hemorrhagic stroke